Optimizing audiovisual itch induction: the role of attention and expectancy. (27th November 2019) - van Laarhoven, A.I.M.; Holle, H.
Abstract : Linked Article:  Marzell et al. Br J Dermatol 2020; 182 :1253–1261 .